Effective management of waste processing as a tool for improving public services and economy in municipality - Fuka, Jan; Baťa, Robert; Šrámková, Lucie (Springer, 2023)
Population growth, together with globalization and urbanization, is leading to an increase in waste production. Waste processing is an essential public service and is becoming an ever-greater challenge in municipal management. This study focuses on sorted waste treatment in the municipal environment of countries of the European Union. Inefficient waste management leads to environmental damage, increases in public budget spending, and distrusts in governments, but intelligent waste management improves the performance of public sector. The aim of this study is to propose an information base and robust public policy tool to manage specific parts of the waste management process, producing a quantification of environmental impacts. The modeling method chosen was the Petri nets, which allows modeling of parallel dynamic processes. The result is a balance of material and energy flows that quantifies environmental impacts resulting from pre-treated waste in relation to the recycling and environmental burden resulting from the energy consumption attributable to this process. The outcomes indicate additional emissions of CO2 in the amount of 4,131.78 kg for 13,762 kWh consumed energy and an overview of another 156 pollutants. In environmental terms, this tool represents an important element in the design of an effective municipal waste management system and information support for developing suitable public policies.
Efektivní řízení nakládání s odpady jako nástroj zkvalitňování veřejných služeb a ekonomiky v obci
Keywords: Dynamic models; Environmental efficiency; Local government services; Management; Municipality; Waste processing; Dynamické modely; environmentální efektivita, služby místní správy; řízení; obec; nakládání s odpady